Odpowiedzi

2009-06-07T15:35:04+02:00
Zad.1
8a+4b/4 = 2a-b

5(a+b)-(b-a)/2 = 5a+5b-b+a/2 = 6a+4b/2 = 2a+2b
2009-06-07T15:35:21+02:00
.przedstaw w jak najprostszej postaci:
a) = 2a+b
b) (5a+5b-b+a)/2=(6a+4b)/2=3a+2b

2.W wyrażeniu 4x²-20x wyłącz przed nawias:
a) x(4x-20)
b)4(x²-5)
c) 4x(x-5)
d)20(1/5x²-x)
e)20x(1/5x-1)
f) -x(-4x+5)
g)-4(-x²+5x)
h)-4x(-x+5)
i)-20(-1/5x²+x)
j)-20x(-1/5x+5)


2009-06-07T15:43:53+02:00
Zad2
a)x(4x-20)
b)4(xkwadrat -5x)
c)4x(x-5)
d)20(1/5 xkwadrat - x)
e)20x(1/5x -1)
f)-x(-4x+20)
g)-4(-xkwadrat+5x)
h)-4x(-x+5)
i)-20(-1/5x kwadrat+x)
j)-20x(-1/5x+1)